Prevalence of being 'At Risk' of Endometrial Carcinoma among Postmenopausal Women in Sri Lanka - Withanage Iresha Udayanagani Jayawickrama; Chrishantha Abeysena (College of Community Physicians of Sri Lanka, 2021)
Introduction: Identifying women who are at risk of developing endometrial carcinoma helps to personalize the management strategies by increasing the survival of high-risk women.   Objectives: To estimate the 'at risk' prevalence and prevalence of selected risk factors for endometrial carcinoma among postmenopausal women in the district of Colombo   Methods: A community-based descriptive cross-sectional study was conducted among 1168 postmenopausal women selected using multistage cluster sampling technique. Women who are 'at risk' for developing endometrial carcinoma was decided based on a cut-off value developed for the set of predictors related to the risk of developing endometrial carcinoma among postmenopausal women.   Results: The prevalence of at risk of endometrial carcinoma was 19.2% (95% CI=17.0-21.6). The prevalence of selected risk factors: physical inactivity 86.2% (95% CI=84.1-88.1), hypertension 37.8% (95% CI=35.1-40.7), diabetes mellitus 39.9% (95% CI=37.1-42.8), early menarche 12.1% (95% CI=10.3-14.1), late menopause 5.7% (95% CI=4.5-7.2), never conceived 7.8% (95% CI=6.3-9.5), generalized obesity 48% (95% CI=45.1-50.9), central obesity 58.6% (95% CI=55.8-61.5), and inadequate servings of vegetables and fruits 69.4% (95% CI=66.8-72.0).   Conclusions & Recommendations: The identification of 'at risk' women who need to be investigated or followed up closely for endometrial carcinoma and the observed high prevalence of selected modifiable risk factors among postmenopausal women warrant population level interventions to curb unhealthy lifestyle practices and advocate relevant stakeholders for prompt action since childhood as a primary prevention measure.